Revisiting the Fluorescence of Benzothiadiazole Derivatives: Anti‐Kasha Emission or Not?. Issue 3 (7th December 2022) - Veys, Koen; de Jong, Flip; Adriaens, Annelies; Coenen, Gitte; Coenen, Kylie; De Ligt, Yvonne; Meysman, Quinten; Paredis, Trijntje; Stalmans, Jesse; Dehaen, Wim; Van der Auweraer, Mark; Escudero, Daniel
Abstract: In this paper we revisit the fluorescent properties of two fluorophores, namely N‐butyl‐7‐(4‐ methoxyphenyl)‐2, 1, 3‐benzothiadiazole‐4‐amine (1 ) and 4‐[[7‐(4‐methoxyphenyl)‐2, 1, 3‐ benzothiadiazole‐4‐yl]amino]‐benzonitrile (2 ), whose emissive and fluorescent sensing properties were recently investigated by Peng et al. in Ref. [1]. Experimentally, these two fluorophores were reported to show excitation wavelength‐dependent emission properties, especially 1, which is a dual emitter. The authors of the original manuscript ascribed the excitation‐wavelength‐dependent emission properties to an emission from a higher‐lying excited state (i. e. anti‐Kasha emission). Our investigations, including steady‐state spectroscopy, lifetime measurements and time‐dependent density functional theory and second‐order algebraic diagrammatic construction [ADC(2)] calculations, unambiguously highlight that the fluorophores do not violate Kasha's rule but reveal instead that a protonated species is responsible for the higher‐lying emissive band. In addition, we have elucidated the actual fluorescent pH sensing mechanisms. More and more molecular systems are reported to violate Kasha's rule; sometimes without compelling proof. This study highlights the need to i) exhaustively investigate apparent anomalous cases reported in the literature that seemingly violate Kasha's rule and ii) propose good scientific practices to correctly assign anomalous photochemical events. Abstract : Computational and spectroscopic investigation of the anomalous fluorescence of two benzothiadiazole derivatives. The originally assigned anti‐Kasha mechanism could not be confirmed, but instead separate emission from a protonated form is suggested.